Silent Splenic Infarction Following Infectious Mononucleosis Associated with Antiphospholipid Antibodies in a Pediatric Patient: A Case Report - Scarponi, Davide; Cosic, Branislava; Fiorilli, Costanza; Di Biase, Anna Rita; Iughetti, Lorenzo (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: The splenic infarction (SI) is a rare complication of infectious mononucleosis (IM), especially in paediatric population. The clinical presentation of this condition can vary widely, but it is most often symptomatic (e.g. pain in the left upper quadrant). Case: We report a case of a previously healthy 12 year old female with a silent splenic infarction (SI) following IM by Epstein-Barr virus (EBV), positive for antiphospholipid anti-cardiolipin IgM antibodies (ACA IgM). Discussion: Numerous pathogenetic mechanisms have been proposed for the SI in the course of IM. The definitive diagnosis of SI is made with CT; in our case, given the lack of urgent clinical indications, the definitive diagnosis was made with MRI. Follow-up was continued using ultrasound and therapeutic management was conservative. Conclusion: We describe a rare case of asymptomatic splenic infarction, in a girl with no underlying predisposing condition. It is important for a pediatrician to be aware of this possible complication and its correct therapeutic management.